Determinants of Digital Transformation in the Post-Covid-19 Business World: Digital Transformation - Tripathi, Shailja (IJRDO - Journal of Business Management, 2021)
Digital technologies are playing a major role in overcoming the impact of the Covid-19 pandemic in business and society. In other words, the pandemic also brings a significant opportunity for digital technologies. Organizations are focusing on managing and adopting strategies for business resiliency and recovery in the post-Covid-19 situation through digital transformation. Business resilience needs processes and people to maintain unremitting business operations. Digital transformation ensures business continuity and helps in running core business operations with resiliency and disaster recovery. This study develops a conceptual framework to understand the determinants of digital transformation in the post-Covid-19 business world. The determinants are categorized based on human, organizational and technology-related factors. These are employee health and safety, virtual collaboration, remote working, business resilience and recovery, business process automation, technology readiness and, cybersecurity risks. This study contributes to applying a conceptual framework of digital transformation in the business during the post-Covid-19 period based on the inclusion of human, organizational and technological factors.